2007
DOI: 10.1091/mbc.e06-09-0797
|View full text |Cite
|
Sign up to set email alerts
|

PP2B-mediated Dephosphorylation of c-Jun C Terminus Regulates Phorbol Ester-induced c-Jun/Sp1 Interaction in A431 Cells

Abstract: The c-Jun/Sp1 interaction is essential for growth factor- and phorbol 12-myristate 13-acetate (PMA)-induced genes expression, including human 12(S)-lipoxygenase, keratin 16, cytosolic phospholipase A2, p21(WAF1/CIP1), and neuronal nicotinic acetylcholine receptor beta4. Here, we examined the mechanism underlying the PMA-induced regulation on the interaction between c-Jun and Sp1. We found that treatment of cells with PMA induced a dephosphorylation at the C terminus of c-Jun at Ser-243 and a concomitant inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 60 publications
3
24
0
Order By: Relevance
“…Overexpression of active CaN (AI domain-deletion of CnA) decreases c-Jun phosphorylation at Ser-243 (Chen et al, 2007). Consistent with our previous result, inhibition of endogenous CaN with siRNA led to increased Ser-243 phosphorylation of c-Jun (Figure 1a), which further verified that CaN targets c-Jun at Ser-243.…”
Section: Calcineurin Interacts With C-jun Within Living Cellssupporting
confidence: 91%
See 4 more Smart Citations
“…Overexpression of active CaN (AI domain-deletion of CnA) decreases c-Jun phosphorylation at Ser-243 (Chen et al, 2007). Consistent with our previous result, inhibition of endogenous CaN with siRNA led to increased Ser-243 phosphorylation of c-Jun (Figure 1a), which further verified that CaN targets c-Jun at Ser-243.…”
Section: Calcineurin Interacts With C-jun Within Living Cellssupporting
confidence: 91%
“…Comparing the binding activities of c-Jun with CnA-DAI and CnA-DAI-CaM, the latter did not bind to c-Jun, which demonstrates the critical role of CaM-binding domain in CaN/c-Jun interaction CaN-mediated Ser-243 dephosphorylation of c-Jun stabilizes the c-Jun protein stability Previously, it has been reported that phosphorylation of c-Jun at Thr-239 and Ser-243 targets c-Jun for polyubiquitination and degradation, and the v-Jun point mutation on Ser-243 allows c-Jun to escape GSK3-dependent recognition and destruction by the E3 ligase (Wei et al, 2005). Additionally, we identified the phosphatase that dephosphorylates Ser-243 of c-Jun is CaN (Chen et al, 2007). We next determined whether CaN participates in regulating c-Jun protein stability through Ser-243 dephosphorylation of c-Jun.…”
Section: Calcineurin Interacts With C-jun Within Living Cellsmentioning
confidence: 76%
See 3 more Smart Citations